PENGARUH BERKEMBANGNYA INDUSTRI PENGOLAHAN RAMBUT TERHADAP TINGGINYA ANGKA PERCERAIAN DI KABUPATEN PURBALINGGA - Nurasih, Wiji (IAIN Purwokerto, 2017)
The writing is about family problem â€œfactory workerâ€in Purbalingga ragency. So many jobs for women replacing job opportunity of men. Cause about 20% men worker from women worker total are worked in industry sector. Many husbands are jobless, otherwise many wives leave their activities as housewife to work in hair processing factory for helping and lightening family economy. So it be the one of important things influencing disharmony in family wich encouraging the high divorce number besides many early marriage factors in Purbalingga regency. This research is done by observation, documentation study and interview. The result is obtained that showing divorce claim from women who feel women have power, while men donâ€™t have economy establishment. Of course, the divorce claim is accompanied various reason causing disharmony in household, cause the wife feels a husband canâ€™t provide for family well.